Intelligent Monitoring of Water Consumption in Urban Environments using Computing and FOG-SWM - Okada, Renan S.; Bezerra, Wesley dos Reis; Westphall, Carlos Becker (Anais do Workshop de Computação Urbana (CoUrb), 2025)
The increasing urbanization has brought significant challenges to water resource management, requiring advanced technological solutions for monitoring and controlling water consumption. In this work, we propose a system based on the FOG-SWM architecture, which combines fog computing and real-time data analysis to optimize water distribution and anomaly detection. We employ data processing and filtering techniques using Python, MapReduce in Pig Latin, and pattern recognition with the Isolation Forest algorithm. The results demonstrate the model's effectiveness in identifying unusual consumption variations and assisting strategic decision-making for urban water sustainability.